2017
DOI: 10.1002/ett.3183
|View full text |Cite|
|
Sign up to set email alerts
|

Leveraging fog computing and software defined systems for selective forwarding attacks detection in mobile wireless sensor networks

Abstract: Selective forwarding is a major problem in wireless sensor networks (WSNs). The nature of sensor environments and the sensitivity of collected measurements in some fields such as war fields increase the need to prevent, detect, or mitigate the problem. One of the most used countermeasures for such problem is the use of voting system based on watchdogs' votes. However, this approach is not applicable in the case of mobile sensors. Mobile WSNs (MWSNs) is growing immensely due to the exposure of applications of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…The issues of security and privacy in fog and mobile edge computing are also a concern that many researchers are considering in their work. The authors of related works have briefly presented these issues and considered some counter measurements. A selective forwarding model that provides monitoring capabilities for detecting malicious nodes and tracing nodes' movements has been presented in the work of Yaseen et al The model has shown huge improvements in terms of detecting malicious nodes by leveraging the fog computing infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…The issues of security and privacy in fog and mobile edge computing are also a concern that many researchers are considering in their work. The authors of related works have briefly presented these issues and considered some counter measurements. A selective forwarding model that provides monitoring capabilities for detecting malicious nodes and tracing nodes' movements has been presented in the work of Yaseen et al The model has shown huge improvements in terms of detecting malicious nodes by leveraging the fog computing infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…García‐Pérez and Merino and Farris et al investigated further into fog computing to reduce the latencies in LTE and 5G networks, respectively, where MSs can be a candidate solution for service deployment. Yaseen et al and de Brito et al discussed leveraging fog computing and SDN for the security of the mobile wireless sensor networks and smart factories.…”
Section: Related Workmentioning
confidence: 99%
“…In [30][31][32], the authors used the power of the fog computing to solve the problem of selective forwarding method in mobile wireless sensor networks to detect different kinds of intrusions. The authors built a model that provided a global monitoring capability based on the infrastructure of the fog computing to trace the movement of sensors and catch malicious ones.…”
Section: Related Workmentioning
confidence: 99%